PENGARUH BEBAN KERJA DAN WORK LIFE BALANCE TERHADAP KINERJA PEGAWAI MELALUI JOB BURNOUT PADA BIRO SDM POLDA BALI - I Ketut Mustika; I Made Agus Rai Perbawa; I Wayan Budi Artha (Journal of Applied Management Studies, 2023)
Management of human resources in an organization is an important aspect, because HR will have a positive impact on organizational development. This study aims to determine and analyze the effect of workload and work life balance on employee performance through job burnout. This research was conducted at the Biro SDM Polda Bali. The population in this study were all employees of the Bali Police HR Bureau with a total of 88 employees. The sample used is the census method so that the entire population is used as a sample. Collecting data using questionnaires. The data analysis technique used is SEM-PLS. The results of this study indicate that workload has a negative and significant effect on employee performance. Work life balance has a positive effect on employee performance. Job burnout has a negative and significant effect on employee performance. Workload has a positive and significant effect on job burnout. Work life balance has a negative and significant effect on job burnout. Job burnout is able to mediate the effect of workload on employee performance. Job burnout is able to mediate the effect of work life balance on employee performance.